A novel framework for Institutional Club Portal (International Journal of Communication Systems and Network Technologies, 2019)
Every educational institute brings enormous opportunities for students to learn and showcase their talent in the form of a number of workshops. These workshops are organized by a number of clubs, societies, technical sub organizations and sub organizations. Each organization has a faculty coordinator, student head and a number of volunteers working under it. The counting is huge when it comes to the number of clubs a college can have and a number of events a club can organize, to there is need for a common portal where student can look for all the events happening in their college under several clubs and be able to enrol for their interested event without much effort at a common place. Clubs portal is one step platform fulfilling the above requirement.
Keywords: Events Registration System; Participant Screening System; Java; Servlets